Optimalisasi Kampung Wisata Kreatif Inovatif Melalui Pemasaran Digital di Kampung Wisata River Tubing Mayangsari Semarang - Masitha Fahmi Wardhani; Diana Puspitasari; Amalia Nur Chasanah; Linda Ayu Oktoriza; Ratna Herawati (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The Mayangsari River Tubing Tourist Village, Semarang is one of the new tours in the city of Semarang, initiated since 2018 by a number of people who are members of the Mayangsari Putra Disaster Preparedness Group (KSB Puma) and the Mayangsari Tourism Awareness Group (Pokdarwis Mayangsari). Starting to only serve the requests of people who are still within the scope of their community or have not yet served the general public, the Culture and Tourism Office of the City of Semarang provides an idea for the development of Mayangsari River Tourism by raising the potential for river tubing attractions, river educational attractions, and culinary tourism attractions. With the progress of the development of the River Tubing tourist village, Mayangsari, which became a finalist for the 2022 great village competition in the category of creative and innovative villages, there were still a number of things that needed to be improved during the investigation stage, namely optimizing digital marketing in making the River Tubing tourist village one of the leading tours. and an independent tourism community that is able to creatively manage the existing innovative potential. Therefore as a solution by providing knowledge and skills in theory and practice of digital marketing in the community of the River Tubing Mayangsari tourism village. The approach method used in this community partnership program is in the form of giving practical lectures in examples of forms of digital marketing that the public can reach and use. It is hoped that the results of this service will be able to add to the mastery of knowledge and skills in theory and practice of digital marketing in the community of the River Tubing Mayangsari tourism village. This addition of knowledge and skills goes hand in hand with the increasing number of tourists who come.